Ecosystem engineering by a canopy‐forming kelp facilitates the recruitment of native oysters. Issue 6 (27th August 2019) - Shelamoff, Victor; Layton, Cayne; Tatsumi, Masayuki; Cameron, Matthew J.; Wright, Jeffrey T.; Johnson, Craig R.
Abstract : Ecosystem engineers are species that influence the abiotic and biotic environment around them and may assist the restoration of associated species, including other habitat‐forming species. We deployed an array of 28 artificial reefs with transplanted Ecklonia radiata, the dominant canopy‐forming kelp species across southern Australia, to investigate how the patch size and density of E. radiata influenced the establishment of the associated communities of plants and animals. Many of the reefs were rapidly colonized by Ostrea angasi, a critically depleted reef‐forming oyster. Over the 24‐month deployment of the reefs, thick oyster mats formed across the entire surface of many of the reefs with estimated biomass densities exceeding 5 kg of live oysters/m 2 ; however, oyster density was dependent on E. radiata patch size and density. Increasing patch size and the presence of kelp resulted in significantly higher densities of oysters 5 months after the reefs were deployed and at the end of the experiment, where oysters were approximately three times more numerous on reefs with kelp compared to those without kelp. E. radiata appeared to facilitate the establishment of O. angasi largely through its capacity to reduce benthic light and thus suppress competition from turfing algae. These results may inform the development of novel approaches to tackle recruitment bottlenecks affecting the restoration of O. angasi reefs.